ILCA's strategy for improving the output of livestock in sub-Saharan Africa based on six research thrusts - Watanabe, S. (1992)
This paper outlines ILCA's strategy of choice, i.e., ILCA's formal mandate, ILCA's altimate goal, the centres' fundamental choice, ILCA's research program for the 1989-93 period, and mode of operation, and research thrusts, and highlights of the achievements. ILCA's research activities concentrate on the three most important ruminant species in Africa-cattle, sheep and goats along the lines of the five-year plan 1989-93. The research is organised into six main areas or thrusts: Cattle milk and meat, Small Ruminant Meat and Milk, Animal Traction, Animal Feed Resoruces, Trypanotolerance and Livestock Policy and Resource use. The first three are `commodity' thrusts; they seek to increase sustainable output of the three most important livestock products, meat, milk and traction. The others are `strategic' thrusts; the information and technology they generate feed intro the commodity thrusts. Within these thrusts, ILCA scientists work in multi-disciplinary teams in collaboration with colleagues in African national programs through networks dedicated to specific research areas. The most successful research achievements have already started to make an impact on smallholder production systems.